2019
DOI: 10.2528/pierl18112804
|View full text |Cite
|
Sign up to set email alerts
|

Higher-Order Moving Target Detection for Rotating Scanning Synthetic Aperture Interferometric Radiometer

Abstract: Since passive millimeter wave synthetic aperture interferometric radiometer (SAIR) has the advantages of high spatial-resolution and large field of view, it is an attractive tool for wide area surveillance. Among the SAIRs, the Rotating Scanning SAIR (RS-SAIR) with linear sparse array is a popular system with low redundancy and high reliability. According to the detection mechanism of RS-SAIR, we extend RS-SAIR to deal with higher-order moving target detection (HMTD) for the first time in this paper. In the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The plane OXY is parallel to the plane oxy, and the distance between the two planes is R. The radiation source S is dispersed into N small parts. The distances between the n-th radiation source S n and antennas c and l are R c n and R l n , respectively [13]. According to [16], the visibility function of the antenna can be expressed as:…”
Section: Data Set Acquisition and Trainingmentioning
confidence: 99%
“…The plane OXY is parallel to the plane oxy, and the distance between the two planes is R. The radiation source S is dispersed into N small parts. The distances between the n-th radiation source S n and antennas c and l are R c n and R l n , respectively [13]. According to [16], the visibility function of the antenna can be expressed as:…”
Section: Data Set Acquisition and Trainingmentioning
confidence: 99%
“…Liu [ 6 ] demonstrated that the root-mean-square error of reconstructed images with targets with rapid brightness temperature (BT) changes, such as tropical cyclones (TCs), was closely related to observation frequency and imaging period. Chen [ 7 ] proposed a method for detecting higher-order moving targets using a rotating scanning SAIR (RS-SAIR) equipped with a linear sparse array. Yang and Hu [ 8 ] utilized the kernel method to predict the observation background by designing a new robust loss function, and a constant false alarm rate (CFAR) detector was used to detect targets.…”
Section: Introductionmentioning
confidence: 99%